2018
DOI: 10.1101/gr.231936.117
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR RNAs trigger innate immune responses in human cells

Abstract: Here, we report that CRISPR guide RNAs (gRNAs) with a 5 ′ -triphosphate group (5 ′ -ppp gRNAs) produced via in vitro transcription trigger RNA-sensing innate immune responses in human and murine cells, leading to cytotoxicity. 5 ′ -ppp gRNAs in the cytosol are recognized by DDX58, which in turn activates type I interferon responses, causing up to ∼80% cell death. We show that the triphosphate group can be removed by a phosphatase in vitro and that the resulting 5 ′ -hydroxyl gRNAs in complex with Cas9 or Cpf1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(129 citation statements)
references
References 29 publications
2
127
0
Order By: Relevance
“…The sgRNAs were synthesised by in vitro transcription (IVT) using T7 RNA polymerase and purified by 10% denaturing urea polyacrylamide gel electrophoresis (PAGE) as described previously (12). A 1000 pmol sample of PAGEpurified sgRNA was treated with 20 U of calf intestine phosphatase (M0525L; New England BioLabs) at 37°C for 3 h to remove the 5' phosphate group to prevent triggering innate immune responses (35). The sgRNA was then extracted with a phenolchloroform-isoamyl alcohol mix and precipitated by isopropanol.…”
Section: Preparation Of Cas9 Protein and Sgrnamentioning
confidence: 99%
See 1 more Smart Citation
“…The sgRNAs were synthesised by in vitro transcription (IVT) using T7 RNA polymerase and purified by 10% denaturing urea polyacrylamide gel electrophoresis (PAGE) as described previously (12). A 1000 pmol sample of PAGEpurified sgRNA was treated with 20 U of calf intestine phosphatase (M0525L; New England BioLabs) at 37°C for 3 h to remove the 5' phosphate group to prevent triggering innate immune responses (35). The sgRNA was then extracted with a phenolchloroform-isoamyl alcohol mix and precipitated by isopropanol.…”
Section: Preparation Of Cas9 Protein and Sgrnamentioning
confidence: 99%
“…) at 98°C for 30 s followed by35 cycles at 98°C for 10 s, 64°C for 30 s, 72°C for 20 s, and a final extension at 72°C for 2 min, followed by holding at 4°C. PCR products were purified using a PCR/Gel Purification Kit (Geneaid, Taipei, Taiwan).…”
mentioning
confidence: 99%
“…While we were preparing this manuscript for submission, the Kim group reported similar results in HeLa cells and primary human CD4 + T cells (38). They confirmed that the type I interferon response is dependent on the presence of a 5’-triphopsphate group and that CIP treatment can increase viability by avoiding the antiviral response.…”
Section: Discussionmentioning
confidence: 74%
“…However, testes -and maybe ovaries -appear to readily accept foreign antigens without the induction of an immune response in several mammals (Simpson 2006;Mellor and Munn 2008;Li et al 2012) , so that germline cells expressing Cas9 may not be eliminated by the immune system. Furthermore, guide RNAs produced from gene drive constructs are not expected to elicit an immune response in vertebrates, as they do not carry 5'-triphosphate ends (Kim et al 2018;Wienert et al 2018) . Clearly, our knowledge in immunology is presently too sparse to anticipate how gene drive systems will interact with the immune system in vertebrates.…”
Section: Probability That the Immune System Does Not Eliminate Cas9-ementioning
confidence: 99%